Encapsulated Oxovanadium(IV) and Dioxovanadium(V) Complexes into Solid Lipid Nanoparticles Increase Cytotoxicity Against MDA-MB-231 Cell Line - Kostrzewa T; Nowak I; Feliczak-Guzik A; Drzeżdżon J; Jacewicz D; Górska-Ponikowska M; Kuban-Jankowska A (International Journal of Nanomedicine, 2023)
Tomasz Kostrzewa,1 Izabela Nowak,2 Agnieszka Feliczak-Guzik,2 Joanna Drzeżdżon,3 Dagmara Jacewicz,3 Magdalena Górska-Ponikowska,1,4,5 Alicja Kuban-Jankowska1 1Department of Medical Chemistry, Faculty of Medicine, Medical University of Gdansk, Gdansk, 80-211, Poland; 2Department of Applied Chemistry, Faculty of Chemistry, Adam Mickiewicz University, Poznań, 61-614, Poland; 3Department of Environmental Technology, Faculty of Chemistry, University of Gdansk, Gdansk, 80-308, Poland; 4IEMEST Istituto Euro-Mediterraneo di Scienza e Tecnologia, Palermo, 90127, Italy; 5Department of Biophysics, Institute of Biomaterials and Biomolecular Systems, University of Stuttgart, Stuttgart, 70174, GermanyCorrespondence: Tomasz Kostrzewa; Alicja Kuban-Jankowska, Department of Medical Chemistry, Faculty of Medicine, Medical University of Gdansk, Gdansk, 80-211, Poland, Tel +48 58 349 14 50, Fax +48 58 349 14 56, Email tomasz.kostrzewa@gumed.edu.pl; alicja.kuban-jankowska@gumed.edu.plIntroduction: Solid lipid nanoparticles (SLN) have been considered lately as promising drug delivery system in treatment of many human diseases including cancers. We previously studied potential drug compounds that were effective inhibitors of PTP1B phosphatase – possible target for breast cancer treatment. Based on our studies, two complexes were selected for encapsulation into the SLNs, the compound 1 ([VO(dipic)(dmbipy)] · 2 H2O) and compound 2 ([VOO(dipic)](2-phepyH) · H2O). Here, we investigate the effect of encapsulation of those compounds on cell cytotoxicity against MDA-MB-231 breast cancer cell line. The study also included the stability evaluation of the obtained nanocarriers with incorporated active substances and characterization of their lipid matrix. Moreover, the cell cytotoxicity studies against the MDA-MB-231 breast cancer cell line in comparison and in combination with vincristine have been performed. Wound healing assay was carried out to observe cell migration rate.Methods: The properties of the SLNs such as particle size, zeta potential (ZP), and polydispersity index (PDI) were investigated. The morphology of SLNs was observed by scanning electron microscopy (SEM), while the crystallinity of the lipid particles was analyzed by differential scanning calorimetry (DSC) and X-ray diffraction (XRD). The cell cytotoxicity of complexes and their encapsulated forms was carried out against MDA-MB-231 breast cancer cell line using standard MTT protocols. The wound healing assay was performed using live imaging microscopy.Results: SLNs with a mean size of 160 ± 25 nm, a ZP of − 34.00 ± 0.5, and a polydispersity index of 30 ± 5% were obtained. Encapsulated forms of compounds showed significantly higher cytotoxicity also in co-incubation with vincristine. Moreover, our research shows that the best compound was complex 2 encapsulated into lipid nanoparticles.Conclusion: We observed that encapsulation of studied complexes into SLNs increases their cell cytotoxicity against MDA-MB-231 cell line and enhanced the effect of vincristine.Keywords: solid lipid nanoparticles, stability of nanoparticles, oxovanadium(IV) and dioxovanadium(V) complexes, triple-negative MDA-MB-231 breast cancer cell line, live imaging microscopy